2021
DOI: 10.1002/jum.15927
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Vein Pulse Wave Spectral Analysis: A Possible Method for Placental Assessment Through Evaluation of Maternal and Fetal Flow Components

Abstract: Objectives-Placental blood flow analysis is complicated by having both maternal and fetal flow components. Using the Fast Fourier Transform (FFT) of the umbilical venous pulse wave spectra (PW) envelope, we could simultaneously assess maternal/fetal blood flow in the placenta and investigate if normal and intrauterine growth restriction (IUGR)/pre-eclamptic pregnancies could be distinguished.Methods-This retrospective study included normal gestations (N = 11) and gestations with IUGR, pre-eclampsia, or both (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Blood flow volume represents the physical aspect of foetal blood access. However, various biochemical substances in the blood play crucial roles as biological and chemical factors for foetal blood and nutrient acquisition, including vascular growth factors and blood sugar ( 32 , 33 ). Scholars from different countries have investigated the biochemical substances in foetal umbilical vein blood flow and concluded that multiple biochemical substances jointly affect foetal weight gain ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow volume represents the physical aspect of foetal blood access. However, various biochemical substances in the blood play crucial roles as biological and chemical factors for foetal blood and nutrient acquisition, including vascular growth factors and blood sugar ( 32 , 33 ). Scholars from different countries have investigated the biochemical substances in foetal umbilical vein blood flow and concluded that multiple biochemical substances jointly affect foetal weight gain ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, low birth weight has recently been suggested as a factor that may help predict the occurrence of cerebral palsy in preterm infants [150]. During chronic hypoxia in the prenatal period, fetal blood flow is selectively redirected to the brain to increase oxygen and nutrient delivery.…”
Section: Effects Of Fetal Growth Restrictionmentioning
confidence: 99%